EFFECTS OF SOWING DATES AND NORMS ON GRAIN QUALITY OF SOYBEAN CULTIVARS (World Bulletin of Social Sciences, 2022)
This paper presents data on the effect of different Sowing dates and norms on grain quality of soybean cultivars. Accordingly, in order to have a high amount of protein and oil content in soybean grain, it is considered appropriate to sow both varieties of soybean in the early period at the norm of 60 kg per hectare. Sowing 15 kg less per hectare (45 kg) than this acceptable rate will reduce protein content by 0.5-0.8%, oil content by 0.3-0.7%, and planting 15 kg more (75 kg) by 0,5-0.6 and 0.3-0.5% less respectively.